2015
DOI: 10.1039/c5ay00835b
|View full text |Cite
|
Sign up to set email alerts
|

Cut-off on demand: adjustment of the threshold level of an immunochromatographic assay for chloramphenicol

Abstract: 15Immunochromatographic assay of small molecules is carried out in a competitive format and is based on the 16 disappearance of analytical zone colouration, as the analyte concentration exceeds a certain threshold level. 17Therefore, the assay of toxic contaminants has the highest information content if this threshold level (cut-off 18 between negative and positive samples) corresponds to the maximum residue limit of the analyte. In this study, 19adjusting the threshold level was investigated for an immunochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
5
22
0
Order By: Relevance
“…Limits of detection of the competing immunoassay (from [55], with additions and amendments). Visual detection can determine whether or not there is staining; detection limit corresponds to point A dividing these options.…”
Section: Figurementioning
confidence: 99%
“…Limits of detection of the competing immunoassay (from [55], with additions and amendments). Visual detection can determine whether or not there is staining; detection limit corresponds to point A dividing these options.…”
Section: Figurementioning
confidence: 99%
“…Barcoded-nanotechnology is used to detect viruses using “barcode lateral flow immune-assay.” A barcode lateral flow immunoassay based on magnetic nanoparticle is used to optimize antibody affinity for a specific antigen. To increase sensitivity and broaden the applications of lateral flow immunoassay, modifications have been made by controlling the cut-off level and insertion of MNPs ( Zvereva et al, 2015 ; Orlov et al, 2016 ). In this way, this assay can be used to diagnose hormones, cardiac and cancer biomarkers, and to detect plant diseases ( Wang L. et al, 2014 ).…”
Section: Biobarcoding and Nanotechnologymentioning
confidence: 99%
“…In Zvereva et al [63], the possibility to change the cut-off level by varying the composition of the hapten-protein and the antibody-(gold nanoparticles) conjugates is considered. Using an example of competitive LFIA of chloramphenicol, it was shown that by reducing the load of immunoreagents on carriers, it was possible to shift the detection limit by two orders of magnitude.…”
Section: Proper Interaction For Lfiamentioning
confidence: 99%
“…In some cases, the developer does not need to achieve maximum sensitivity but to fix the threshold that separates the positive and negative results in accordance with the regulatory requirements for MRLs. This allows the composition of conjugates used in the analysis discussed above to be varied [63]. A qualitative "yes-no" analysis can be transformed into a semiquantitative one with a change in the number of colored bands corresponding to several threshold levels.…”
Section: Proper Output For Lfiamentioning
confidence: 99%